2020
DOI: 10.1111/eci.13317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atrial fibrillation in critically ill patients admitted to a stepdown unit

Abstract: Background: Limited data are available on the clinical course of patients with history of atrial fibrillation (AF) when admitted in an intensive care environment. We aimed to describe the occurrence of major adverse events in AF patients admitted to a stepdown care unit (SDU) and to analyse clinical factors associated with outcomes, impact of dicumarolic oral anticoagulant (OAC) therapy impact and performance of clinical risk scores in this setting. Materials and methods: Single-centre, observational retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…AFICILL (Atrial Fibrillation In Critically ILL) is a retrospective cohort study enrolling medical critically ill patients affected by pre-existing AF admitted to the SDU of the internal and sub-intensive medicine department of the Azienda Ospedaliero-Universitaria “Ospedali Riuniti”, Ancona, Italy. Full details regarding the data collection procedure are reported in a previous paper 5 : we retrospectively considered a cohort of critically ill patients with pre-existing AF admitted to the internal medicine department of the Azienda Ospedaliero-Universitaria “Ospedali Riuniti”, Ancona, Italy. This department implemented, since January 01st 2002, an electronic medical record system (eMRS) for inpatients’ management.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AFICILL (Atrial Fibrillation In Critically ILL) is a retrospective cohort study enrolling medical critically ill patients affected by pre-existing AF admitted to the SDU of the internal and sub-intensive medicine department of the Azienda Ospedaliero-Universitaria “Ospedali Riuniti”, Ancona, Italy. Full details regarding the data collection procedure are reported in a previous paper 5 : we retrospectively considered a cohort of critically ill patients with pre-existing AF admitted to the internal medicine department of the Azienda Ospedaliero-Universitaria “Ospedali Riuniti”, Ancona, Italy. This department implemented, since January 01st 2002, an electronic medical record system (eMRS) for inpatients’ management.…”
Section: Methodsmentioning
confidence: 99%
“…While both CHA 2 DS 2 -VASc and HAS-BLED scores are almost universally recognized as the mainstay for the baseline evaluation of the “usual” AF patients, observational data suggest that the predictive ability of such scores is extremely limited in critically ill patients, due to the complex clinical status and to the overall clinical severity 5 . Despite this, and in absence of specifically-designed risk scores, stratification with CHA 2 DS 2 -VASc and HAS-BLED is still recommended by experts also in critical illness 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported AF outcomes for critically ill patients admitted to step down units. CHA 2 DS 2 -VAS c scores were not associated with the occurrence of stroke or TIA and failed to predict these thromboembolic events 14 .…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…13 A recent retrospective study showed that CHA 2 DS 2 -VASc and HAS-BLED scores were not associated with stroke or major bleeding and were unable to predict these events. 14 Therefore, decisions around anticoagulation strategies in critical care populations are complex and challenging. There are currently no recommendations relating specifically to the rational therapy of AF in the critical care setting.…”
Section: Introductionmentioning
confidence: 99%
“…1 Even in the context of acutely ill patients in ICUs or sub-intensive/stepdown units, the presence or the occurrence of AF very often complicates clinical management and has an impact on the burden of adverse clinical outcomes. [2][3][4] Despite the relevant impact of AF in the management of acutely ill patients, looking at the major clinical guidelines about both AF and sepsis, we can find a general lack of consideration about this clinical issue and an overall absence of specific recommendations. 1,5,6 Among the various aspects related to the treatment of patients with AF, the choice of and management of rate control drugs play important roles in the optimization and integrated care of these patients.…”
mentioning
confidence: 99%